2010
DOI: 10.1155/2010/687547
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Polyarteritis Nodosa in Childhood: A Case Report and Review of the Literature

Abstract: Polyarteritis nodosa is a rare vasculitis of childhood. Cutaneous PAN (cPAN) is limited to the skin, muscles, joints, and peripheral nerves. We describe a 7.5-year-old girl with cPAN presenting initially as massive cervical edema who later went on to develop subcutaneous nodules, livedo reticularis, myositis, arthritis, and mononeuritis multiplex. The use of corticosteroids resulted in initial clinical improvement, but symptom recurrence necessitated disease modifying antirheumatic drugs and biologic therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 43 publications
(19 reference statements)
1
25
0
Order By: Relevance
“…In particular, when considering a looser definition of "cutaneous PAN", as also proposed in many other publications [11,13,16,26], we found a few cases where children with "cutaneous PAN" and no visceral involvement went on to develop severe complications, such as digital necrosis, ending up with extended periods of glucocorticoid therapy and immunosuppressive drugs and having long-lasting disease activity. We conclude that the organ distribution-based distinction between cutaneous and visceral childhood PAN had little prognostic power in this series.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In particular, when considering a looser definition of "cutaneous PAN", as also proposed in many other publications [11,13,16,26], we found a few cases where children with "cutaneous PAN" and no visceral involvement went on to develop severe complications, such as digital necrosis, ending up with extended periods of glucocorticoid therapy and immunosuppressive drugs and having long-lasting disease activity. We conclude that the organ distribution-based distinction between cutaneous and visceral childhood PAN had little prognostic power in this series.…”
Section: Discussionsupporting
confidence: 55%
“…In adults, cutaneous PAN likely appears as an indolent disease, and some authors limit the definition of cutaneous PAN to cutaneous involvement without fever, myalgia, arthralgia or peripheral neuropathy (except if present at the same localization as skin lesions) [12]. In contrast, a review of 119 children with cutaneous PAN found that most children had fever and elevated acute-phase reactants, and that musculoskeletal features, joint involvement and peripheral neuritis were frequent (43%, 58% and 18%, respectively) [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, CPAN is uncommon in children; there are only approximately 140 cases in the literature [3]; and sibling cases have never been reported. Therefore, our siblings' cases might suggest the possibility that E148Q MEFV mutation and/or HLA-A24, -DR15 alleles could influence the development of CPAN, although these commonly observed HLA alleles might not be the major factor for the onset in siblings.…”
Section: Discussionmentioning
confidence: 99%
“…kidney, heart, and liver [1][2][3]. Clinical manifestations of CPAN include tender subcutaneous nodules, livedo reticularis, cutaneous ulcers, and necrosis [1,2].…”
Section: Introductionmentioning
confidence: 99%